2019
DOI: 10.20945/2359-3997000000145
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytoma and paraganglioma: implications of germline mutation investigation for treatment, screening, and surveillance

Abstract: Objective: Paraganglioma (PGL) and pheochromocytoma (PCC) are rare neuroendocrine tumors that were considered to be predominantly sporadic. However, with the identification of novel susceptibility genes over the last decade, it is currently estimated that up to 40% of cases can occur in the context of a hereditary syndrome. We aimed to characterize PGL/PCC families to exemplify the different scenarios in which hereditary syndromes can be suspected and to emphasize the importance for patients and their families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
1
4
0
1
Order By: Relevance
“…Loss of SDHB staining was present in 19 specimens (36%), suggesting the presence of SDHB -associated PPGL in these cases [ 12 ]. The prevalence noted in this study is similar to that reported globally and serves to illustrate that many cases of heritable PPGL likely remain undetected in sub-Saharan Africa [ 13 , 14 ]. The paucity of reports from sub-Saharan Africa may be attributed to the limited health care resources and the lack of availability of genetic testing in the region [ 7-9 , 11 ].…”
supporting
confidence: 83%
“…Loss of SDHB staining was present in 19 specimens (36%), suggesting the presence of SDHB -associated PPGL in these cases [ 12 ]. The prevalence noted in this study is similar to that reported globally and serves to illustrate that many cases of heritable PPGL likely remain undetected in sub-Saharan Africa [ 13 , 14 ]. The paucity of reports from sub-Saharan Africa may be attributed to the limited health care resources and the lack of availability of genetic testing in the region [ 7-9 , 11 ].…”
supporting
confidence: 83%
“…Genetic testing is gaining popularity among the specialists treating PGN, because 20-40% of them have hereditary mutations 12 . Succinate dehydrogenase genes (SDHx A to F), MAX, and TMEM127 are novel genes have been related to "emerging hereditary PHEO/PGN syndromes, " which may be more frequent than the traditionally known genes that cause cancer susceptibility syndromes, such as VHL, NF-1 (neurofibromin 1), and RET (ret proto-oncogene) 23 . New algorithms suggest that HNPGN should be tested for SDHD, SDHC, VHL, SDHB, or SDHAF2 sequentially, unless other characteristics are present (multicentricity, specific syndrome, or family history or malignant behavior) 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In our patient, genetic testing revealed PGL4 syndrome associated with the Arg230His mutation in the SDHB gene. The mutation was reported previously (21), including in familial cases, although to date, there are only a few families bearing the Arg230His mutation described in the literature (22)(23)(24)(25).…”
Section: Set Of Primers For Pcr Amplification Of the Evaluated Gene Exonsmentioning
confidence: 95%